The Effect of Service Quality and Excellence in Islamic Insurance Products on Community Preferences in Choosing an Islamic Insurance Company in Sikara Kara 1 Village, Natal Kab. Madina - Lestari, eka; Jannah, Nurul; Nasution, Juliana (International Journal of Finance Research, 2023)
In order to determine the influence of service quality and perfection in Islamic insurance products on preferences in choosing Islamic insurance firms in Sikara kara 1 village, Natal kab. Madina, this study uses a quantitative technique based on the theory of causal connection research. Likert-scale research questionnaires were distributed via Google Forms in order to gather data for the study. Among the data analysis and testing techniques used in research are determinant coefficient tests (R2), multiple linear regression analysis, significance tests, validity and reliability tests, and tests based on conventional assumptions. This study employed random sampling, meaning that samples from the population were randomly selected. The 1564 residents of the Sikara Kara 1 village community make up the study's population. Since more than a thousand people are in the study population, the researchers used the Slovin approach to choose a sample. At that point, there were 94 people in the sample. The findings demonstrated that community decisions are significantly impacted by service quality. With a t value of 1.696 greater than t table 1.661 with a significant value of 0.004 less than 0.05 and a t count of 4.629 greater than t table 1.661 with a significant value of 0.000 less than 0.05, the computations' results demonstrate that the product's second benefit significantly influences people's preferences. It is often recognized that people's preferences are favorably and considerably influenced by elements like perfection and quality of service while choosing an insurance company in Sikara Kara 1 Village, Natal Kab. Madina